Wound Healing Current Perspectives - Hakan Dogan, Kamil (IntechOpen, 2019)
Wound healing and its treatment are subjects that have been discussed for centuries in the medical literature. Wounds are everywhere, occurring in the young and elderly and in hospital and at home, and affect patients in every clinical specialty around the world. There are many publications on wound healing, but this book intends to give an overview of its current perspectives so as to be useful to practice care in wound healing and to improve the quality of life. It is considered that this book will be useful for clinicians who are interested in wound care.